Referential coherence: children’s understanding of pronoun anaphora : insights from mono- and bilingual language acquisition - Klages, Hana; Gerwien, Johannes (Referential and relational discourse coherence in adults and children, 2020)
Das Kapitel Referential coherence: Children’s understanding of pronoun anaphora. Insights from mono- and bilingual language acquisition erschien in Referential and Relational Discourse Coherence in Adults and Children auf Seite 105.
Gesehen am 13.04.2022